Analisis Kebijakan Pemerintah Daerah dalam Penanganan Kesehatan Masyarakat - Irman Puansah; Anggi Aulia Hutasuhut; Melisa Aulia Koto; Nurhamida Fitri Simatupang; Muri Entia Melati Lubis (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Public health is an important indicator of the success of regional development and the quality of public services. Local governments play a strategic role in the provision of healthcare services through adaptive, effective, and community-oriented policies. This study aims to analyze local government policies in addressing public health issues through a literature review approach. The research method employed a literature study by examining scientific journals, laws and regulations, books, and policy documents related to regional health policies in Indonesia. The findings indicate that regional health policies are influenced by decentralization, fiscal capacity, the quality of governance, and inter-institutional synergy. Policy implementation continues to face several challenges, including limited budgets, low quality of healthcare human resources, unequal access to healthcare services, and weak intersectoral coordination. However, public service innovation and the strengthening of good governance have proven effective in improving healthcare service delivery. This study emphasizes that the success of regional health policies is determined by government commitment, community participation, integration between central and local policies, institutional strengthening, budget optimization, and service innovations based on community needs.